Stop Patriarchy Is A Key To Preventing Stunting: A Qualitative Study Of Indigenous Peoples In Central Maluku Regency - Marasabessy, Nur Baharia; Tuhumena, Femi Serly; Rauf, Saidah (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Stunting among children under five remains a major public health problem in Indonesia, particularly within indigenous communities where social, cultural, and gender structures strongly influence caregiving practices. Despite numerous nutrition-specific interventions, the persistence of stunting suggests the presence of deeper sociocultural determinants, particularly patriarchal norms and unequal gender roles that affect maternal and child well-being. This qualitative case study was conducted from July to October 2023 in three indigenous villages of Central Maluku Regency: Ulahahan (coastal), Piliana, and Elemata (mountainous). Participants (n=34) were purposively recruited, including mothers of stunted children, community and traditional leaders, religious representatives, and healthcare providers. Data were collected through 30 in-depth interviews and four focus group discussions (FGDs), transcribed verbatim, and analyzed thematically. Five interlinked themes emerged: (1) child-related factors (irregular eating, non-exclusive breastfeeding, recurrent illness); (2) cultural practices (traditional birth attendants, early introduction of porridge/papeda); (3) patriarchal norms and gender roles (domestic labor as “women’s oath,” pamali prohibitions on men doing “women’s work,” women’s double burden despite agricultural labor); (4) economic constraints (carbohydrate-heavy diets, low protein access, reliance on subsistence farming and social assistance); and (5) maternal factors (short birth intervals, early marriage, limited ANC, stress). Descriptively, most stunted children were aged 25–59 months (79.4%) and male (67.6%); 70.6% of mothers married before 20 years of age, and 82.3% had primary education or less. Stunting in these settings is embedded in patriarchal cultural systems that institutionalize unequal household responsibilities and constrain maternal time, autonomy, and caregiving quality. Gender-transformative, community-based strategies, such as engaging men and customary leaders, promoting equitable domestic roles, strengthening women’s economic and decision-making power, and integrating gender-sensitive nutrition approaches, are essential to reduce stunting.